Empire and belonging in the Eurasian borderlands - Goff, Krista A.; Siegelbaum, Lewis H. (Cornell University Press, 2019)
The various chapters in this volurne address questions of belonging in multiethnic, bounded political spaces. They range across the Ottoman Empire in Anatolia, Kemalist Turkey, Imperial Russia, and the Soviet Union, from the mid-19th to the late 20th centuries. The first section focuses on eliminations: the taking of Geok-Tepe, stronghold of the Tekke Turkmen, in 1881 and the Russian empire's expansion into Central Asia; the 1916 revolt in Semirech'e (in modem-day Kazakhstan); the Armenian genocide viewed in comparative perspective; and expulsions in the postwar Caucasus. The second looks at imperial standardization: in Soviet Armenia, modernizing state officials accommodated Armenian linguistic and cultural particularities as local actors debated the terms of Sovietization; meanwhile, the Tatar lexical revolution was inspired by Soviet attempts to enlighten 'backward peoples.' The third part looks at connections between belonging and myth making: the origins of the notion of a "Sovetskii Narod" in the experience of the Great Patriotic War; Gamsakhurdia's assertion of Georgia's status as a quintessential and foundational European nation. The various contributions to the book illustrate both the mutability and the durability of imperial belonging in the Eurasian borderlands. Once considered part of the 'Eastern Question,' the minority peoples of the Russian/Soviet and Ottoman empires are shown to have had their own longings and identities; their capacity to push back against but also selectively absorb imperial initiatives makes them fascinating subjects of belonging